A review of bioanalytical methods for chronic lymphocytic leukemia drugs and metabolites in biological matrices. (26th December 2019) - P S, Suresh; Trivedi, Ravi Kumar; Srinivas, Nuggehally R.; Mullangi, Ramesh
Abstract: Quantitation of drugs used for the treatment of chronic lymphocytic leukemia in various biological matrices during both pre‐clinical and clinical developments is very important, often in routine therapeutic drug monitoring. The first developed methods for quantitation were traditionally done on LC in combination with either UV or fluorescence detection. However, the emergence of LC with mass spectrometry in tandem in early 1990s has revolutionized the quantitation as it has provided better sensitivity and selectivity within a shorter run time; therefore it has become the choice of method for the analysis of various drugs. In this article, an overview of various bioanalytical methods (HPLC or LC–MS/MS) for the quantification of drugs for the treatment of chronic lymphocytic leukemia, along with applicability of these methods, is given.